2016
DOI: 10.1007/s12639-016-0838-6
|View full text |Cite
|
Sign up to set email alerts
|

Some probable factors affecting the malaria situation before and at the beginning of a pre-elimination program in southeastern Iran

Abstract: The area southeast of Iran still copes with malaria as an unstable infectious disease and includes the most autochthonous malaria reports in the country. This comprehensive study was carried out for the evaluation of environmental factors, welfare indicators and health facilities on the malaria situation before and at the beginning of a pre-elimination programme in this area. The probable factors affecting the malaria situation, including the water-pipe network, electricity, rainfall, long-lasting integrated n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…While the region does not possess numerous water bodies ( 12 ), cement water tanks (ponds,) as usual water sources especially in rural areas, could be considered mosquitoes breeding places. The humidity in this region is mainly due to the Bengal Gulf streams, which come to Iran only in the summer ( 15 ). Despite the growing of date palm gardens, small farms, and even paddy fields in this province ( 11 ), the normalized difference vegetation index (NDVI) shows a thin vegetation cover ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…While the region does not possess numerous water bodies ( 12 ), cement water tanks (ponds,) as usual water sources especially in rural areas, could be considered mosquitoes breeding places. The humidity in this region is mainly due to the Bengal Gulf streams, which come to Iran only in the summer ( 15 ). Despite the growing of date palm gardens, small farms, and even paddy fields in this province ( 11 ), the normalized difference vegetation index (NDVI) shows a thin vegetation cover ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the malarious areas of Iran, the majority of the malaria vectors are endophilic; therefore, an appropriate approach for controlling Anopheles mosquitoes is the application of IRS in the houses ( 58 ). The high effectiveness of IRS in the control of malaria is the main reason that Iranian government accepted IRS as one of the main control methods.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the current study found that most migrants have no access to them. Although there is a policy of distributing free LLINs in the malaria elimination program in Iran [ 27 ], this protection tools do not cover all areas. However, migrants who had access to malaria protection tools; stated that they received it from the health system.…”
Section: Discussionmentioning
confidence: 99%